Requirements for the Leader in the Management of the Preschool Educational Organization on the Basis of Innovative Approaches - Temirov Anvar Amir (Zien Journals, 2023)
The article analyzes the organizational and economic mechanisms of the development of small business and private entrepreneurship in rural areas, and gives conclusions and recommendations This article describes the requirements, qualities and tasks of the head of the preschool educational organization in managing the pre-school educational organization using innovative approaches, as well as the specific features of management.
Keywords: Competence; competent; innovation; aspect